Managing the Effects of Noise From Ship Traffic, Seismic Surveying and Construction on Marine Mammals in Antarctica - Erbe, Christine; Dähne, M.; Gordon, J.; Herata, H.; Houser, D.S.; Koschinski, S.; Leaper, R.; McCauley, Robert; Miller, B.; Müller, M.; Murray, A.; Oswald, J.N.; et al. (FRONTIERS MEDIA SA, 2019)
© 2019 Erbe, Dähne, Gordon, Herata, Houser, Koschinski, Leaper, McCauley, Miller, Müller, Murray, Oswald, Scholik-Schlomer, Schuster, Van Opzeeland and Janik.